Interaction Between Two Charged-Hardcore Soft Particles - Bui, Quyen Thi Le; Ngo, Thien Duc; Nguyen, Thuy Thi Phuong; Nguyen, Hoai Thi Lam (Communications in Physics, 2017)
During two last decades, theories of soft-particles has been introduced and developed in order to describe the behavior of bacteria and virus which can be considered as the bio-colloid particles. Soft particles are assumed to be consist of a rigid core inside an ion-permeable shell. The outer layer is always negatively charged while the core can be neutral or charged. In this paper, we investigate the interaction between two identical soft-particles with charged core. We derived the analytic formula for the interaction energy in a compact form. We showed that this interaction energy involving a screened Coulomb-like interaction term with a distance-independent coefficient. The numerical calculations showed that the interaction energy has very small amplitude and exponentially decay on the distance between the soft particles. The results indicate that it is possible to measure this kind of interaction energy when the system is put into a salt solution with the concentration low enough.